EVALUATING LACTOFERRIN AND CALPROTECTIN AS MARKERS OF INTESTINAL INFLAMMATION INCHRONIC PANCREATITIS - Claudia Teresa CARVENTE; Maria Lúcia Cardoso Gomes FERRAZ; Carlos Fischer de TOLEDO (Arquivos de Gastroenterologia, 2024)
ABSTRACT Background: The treatment of chronic pancreatitis does not consistently solve intestinal abnormalities, and despite the implementation of various therapeutic measures, patients often continue to experience persistent diarrhea. Therefore, it is imperative to recognize that diarrhea may stem from factors beyond pancreatic insufficiency, and intestinal inflammation emerges as a potential contributing factor. Objective: The aim of this study was to assess fecal lactoferrin and calprotectin levels as indicators of intestinal inflammation in patients with chronic pancreatitis experiencing persistent diarrhea. Methods: In this study, 23 male patients with chronic pancreatitis primarily attributed to alcohol consumption and presenting with diarrhea (classified as Bristol stool scale type 6 or 7), underwent a comprehensive evaluation of their clinical and nutritional status. Fecal lactoferrin and calprotectin levels were measured utilizing immunoassay techniques. Results: The average age of the participants was 54.8 years, 43.5% had diabetes, and 73.9% were smokers. Despite receiving enzyme replacement therapy and refraining from alcohol for over 4 years, all participants exhibited persistent diarrhea, accompanied by elevated calprotectin and lactoferrin levels indicative of ongoing intestinal inflammation. Conclusion: The findings of this study underscore that intestinal inflammation, as evidenced by elevated fecal biomarkers calprotectin and lactoferrin, may contribute to explaining the persistence of diarrhea in patients with chronic pancreatitis.